Pengaruh DER dan TATO terhadap Return Saham dengan ROA sebagai Mediasi, CSR Disclosure sebagai Moderasi dan Firm Size sebagai Kontrol pada Perusahaan Subsektor Basic Materials di BEI - Alya Badariah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Companies in the Basic Materials sector on the Indonesia Stock Exchange experienced a misalignment between financial performance and market performance during the 2021-2024 period, where fluctuations in profitability were not always followed by proportional movements in stock returns. This study aims to analyze the effect of capital structure (DER) and asset efficiency (TATO) on stock returns, with ROA as a mediating variable, CSR disclosure as a moderating variable, and firm size as a control variable. Theoretically, this study uses Agency Theory as the main framework to explain the relationship between leverage, asset efficiency, profitability, and stock returns through agency costs and transmission mechanisms. Stakeholder Theory also uses Stakeholder Theory to explain the moderating role of CSR disclosure in strengthening social legitimacy and reducing information asymmetry in the Basic Materials sector, which has significant environmental impacts and faces mandatory CSR regulations. Methodologically, it tests the moderated mediation mechanism where CSR disclosure moderates the ROA mediation pathway. The study used panel data regression analysis on 51 Basic Materials companies (204 observations) for the 2021-2024 period using EViews 13 software, including classical assumption tests, panel model selection, hypothesis testing, and Moderated Regression Analysis (MRA). The findings of this study show that DER has a significant negative effect on ROA, while TATO has no significant effect. ROA fully mediates the effect of DER on stock returns. CSR disclosure acts as a weak moderator, only moderating the relationship between profitability and stock returns. CSR weakens the direct relationship between ROA and Return but strengthens the indirect effect of DER and ROA through a double negative effect. Moderated mediation tests confirm that CSR disclosure moderates the indirect path only at the final stage (second-stage moderated mediation). Overall, profitability is the dominant factor influencing stock returns, with capital structure operating through the profitability mediation mechanism, while CSR disclosure plays a limited role as a moderator that alters the dynamics of market response.